Exploring the trends of breathlessness and mortality in conjunction with AQI in India’s coal capital, Dhanbad - Jha, Ravi Ranjan; Kumar, Vivek; Tiwari, Abhishek; Singh, Shivendra Kumar; Shreshtha, Samar; Rana, Rishabh Kumar (Indian Journal of Community Health, 2023)
Background: Air Quality Index (AQI) has been evidenced to be linked with various health problems including NCDs. Globally, the combined effect of ambient air and household air pollution causes 6.7 million premature deaths. Objective: A study was undertaken to understand various associations of AQI and morbidity data, indigenous to the coal capital region of India. Methodology: This was a cross-sectional study where district AQI data was obtained from the state of Jharkhand while mortality and morbidity data were collected from our medical college. MS Excel and SPSS were used to analyse the data. Results: During the study period, the AQI of Dhanbad has been moderate to poor. The lowest AQI was noted in May 2020 at 105 while the highest in June 2019 at 217. The highest admission, due to respiratory illness, was noted in May 2020 with AQI of 105. Using univariate analysis age categorisation was statistically significant, as the respiratory illness was highest in >85 years age group. In logistic regression, it has the highest odds of 2.9 (1.5-5.5). Conclusion: This region-specific indigenous information is expected to provide a valuable tool for Air quality managers for more focused action. It also highlights the health impacts of the worsening air quality.